(untitled) (Journal of Scientific Research, 2013)
The effect of Ganoderma lucidum in paracetamol-induced acute hepatotoxicity was investigated on Wistar rats in the present study. Hepatotoxicity was induced by oral administration of paracetamol (500 mg/kg of body weight) for 7 consecutive days. The extent of liver damage was studied by assessing biochemical parameters comprising of plasma aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH), total bilirubin (TB) and total plasma total protein (TP). Oral administration of paracetamol significantly increased the plasma levels of AST, ALT, ALP and LDH with concomitant decrease of TP. The feeding of G. lucidum (1% powder with basal food) significantly reversed the plasma levels of ALT, AST, ALP, LDH, and TP nearly to those of the normal rats. Thus, the results of the present demonstrate that the G. lucidum has significant hepatoprotective activity against paracetamol induced acute hepatotoxicity in rats.